Concept of Sadhus in Nepalese Society - Khatiwada, Som Prasad (Researcher: A Research Journal of Culture and Society, 2014)
The concept of Sadhus is an old Hindu tradition started long ago from the system of Ashram in Indian Sub-continent. In general, human life is divided into four stages and the last stage is known as Sanyasa. When an old person becomes free from his family responsibilities then he practices peaceful activities. This stage of life is called Sanyasa and it is a form of Sadhu. Sadhus generally live in Asharams or temples in the group. In the past, they were forced to take weapons in their hands for the protection of their life and religion. Therefore, Akhadas were established in the place of ashramas to keep militant Sadhus. They do not have to keep greed, love, exceptions and trishna and their Yajnas should relate on the well-being of the universe. They are the means of study and they should be utilized to attract tourists in modern economic world. DOI: http://dx.doi.org/10.3126/researcher.v1i2.9888 Researcher 1(2) 2013: 81-103